FILOSOFI HUMAN CAPITAL DAN PEMBERDAYAAN SEBAGAI FONDASI PENGEMBANGAN SDM PENDIDIKAN - Bambang Setiono; Supriyadi; Anggy Hanggara; Muhammad Amir Masruhim; Warman; Dwi Nugroho Hidayanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the philosophy of Human Capital and empowerment as strategic foundations for developing human resources (HR) in education. Using a systematic literature review of 42 recent scholarly sources, the study identifies that Human Capital strengthens educational personnel capacity through the development of knowledge, skills, and professional competence, while empowerment activates this capacity through autonomy, participation, intrinsic motivation, and organizational support. The findings reveal that integrating both approaches enhances educator performance, creativity, and innovation, while also strengthening educational organizational culture. The integrative Human Capital–Empowerment model developed in this study highlights that the quality of education is significantly influenced by the synergy between capacity building and empowerment mechanisms. This research offers theoretical contributions to educational management and practical recommendations for designing effective and sustainable HR development strategies in educational institutions.